2013
DOI: 10.1002/ejoc.201301383
|View full text |Cite
|
Sign up to set email alerts
|

Highly Diastereoselective Esterification of Ketenes Generated In Situ from Acyl Chlorides with (R)‐Pantolactone Derivatives

Abstract: Our mechanistic investigations have revealed that Et3N is a key requirement for the highly diastereoselective formation of esters from the corresponding acyl chlorides with (R)‐pantolactone via ketene‐derived complexes. Furthermore, we have discovered that (R)‐N‐benzyl‐pantolactam is a more effective chiral alcohol than (R)‐pantolactone for the esterification of in situ generated ketenes.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 34 publications
0
4
0
Order By: Relevance
“…Secondary and tertiary alcohols in positions α to amide or ester groups are efficiently reduced as shown in Scheme . Remarkably, Yamagami et al demonstrated that this process could be easily scale‐up to a kilogram‐scale to generate an advanced intermediate in the synthesis of a potent glucokinase activator (GKA) .…”
Section: Iodine‐atom‐mediated Deoxygenationmentioning
confidence: 99%
See 2 more Smart Citations
“…Secondary and tertiary alcohols in positions α to amide or ester groups are efficiently reduced as shown in Scheme . Remarkably, Yamagami et al demonstrated that this process could be easily scale‐up to a kilogram‐scale to generate an advanced intermediate in the synthesis of a potent glucokinase activator (GKA) .…”
Section: Iodine‐atom‐mediated Deoxygenationmentioning
confidence: 99%
“…Cyanohydrines are also converted into the deoxygenated products although the reaction substrates may decompose partially in the reaction mixture to give the corresponding ketones. [30b]…”
Section: Iodine‐atom‐mediated Deoxygenationmentioning
confidence: 99%
See 1 more Smart Citation
“…Among them, small-molecule glucokinase activators (GKAs) represent a new strategy . ( R )-2-[4-(Cyclopropylsulfonyl)phenyl]- N -pyrazin-2-yl-3-(tetrahydro-2 H -pyran-4-yl) propanamide ( R )-1 has been regarded as a potent GKA . For use in nonclinical studies and clinical trials, Prosidion developed a scalable methodology using the enantioselective hydrogenation of acrylic acid ( E )-3 as a key reaction for the construction of stereochemistry at the α-carbon center to give the key intermediate ( R )-2 , followed by amidation with 2-aminopyrazine, giving ( R )-1 (Scheme , route a). , According to their reaction conditions, a high pressure (>700 psig) of hydrogen was required to promote the reaction.…”
Section: Introductionmentioning
confidence: 99%